Pengaruh Penerapan Prinsip Good Corporate Governance Dan E-Service Quality Terhadap Minat Mahasiswa Fakultas Ekonomi Dan Bisnis Islam Uin Khas Jember Dalam Bertransaksi Pada Bank Syariah Indonesia - Muhammad Khanifan Abdillah; Retna Anggitaningsih (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyze the influence of the principles of Good Corporate Governance (GCG) and E-Service Quality on the interest of FEBI UIN KHAS Jember students in making transactions at Bank Syariah Indonesia (BSI). The approach used is quantitative with associative research type. The data collection technique was carried out by distributing questionnaires to 86 respondents selected using the Slovin formula. The results of the study showed that both GCG and E-Service Quality partially and simultaneously had a significant effect on students' interest in making transactions at BSI. This finding reinforces the importance of good governance and digital service quality in increasing students' interest as a digital generation in choosing Islamic banking services.